Oral fosfomycin for the treatment of lower urinary tract infections among kidney transplant recipients—Results of a Spanish multicenter cohort. Issue 2 (28th October 2019) - López‐Medrano, Francisco; Silva, José Tiago; Fernández‐Ruiz, Mario; Vidal, Elisa; Origüen, Julia; Calvo‐Cano, Antonia; Luna‐Huerta, Enrique; Merino, Esperanza; Hernández, Domingo; Jironda‐Gallegos, Cristina; Escudero, Rosa; Gioia, Francesca; et al.
Abstract : Oral fosfomycin may constitute an alternative for the treatment of lower urinary tract infections (UTIs) in kidney transplant recipients (KTRs), particularly in view of recent safety concerns with fluroquinolones. Specific data on the efficacy and safety of fosfomycin in KTR are scarce. We performed a retrospective study in 14 Spanish hospitals including KTRs treated with oral fosfomycin (calcium and trometamol salts) for posttransplant cystitis between January 2005 and December 2017. A total of 133 KTRs developed 143 episodes of cystitis. Most episodes (131 [91.6%]) were produced by gram‐negative bacilli (GNB), and 78 (54.5%) were categorized as multidrug resistant (including extended‐spectrum β‐lactamase‐producing Enterobacteriaceae [14%] or carbapenem‐resistant GNB [3.5%]). A median daily dose of 1.5 g of fosfomycin (interquartile range [IQR]: 1.5‐2) was administered for a median of 7 days (IQR: 3‐10). Clinical cure (remission of UTI‐attributable symptoms at the end of therapy) was achieved in 83.9% (120/143) episodes. Among those episodes with follow‐up urine culture, microbiological cure at month 1 was achieved in 70.2% (59/84) episodes. Percutaneous nephrostomy was associated with a lower probability of clinical cure (adjusted odds ratio: 10.50; 95% confidence interval: 0.98‐112.29; P = 0.052). In conclusion, fosfomycin is an effective orally available alternative for treating cystitis among KTRs. Abstract : Fosfomycin can be considered a first choice alternative for the treatment of cystitis in kidney transplant recipients, particularly in view of recent safety concerns with fluoroquinolones.